Typhoid fever in children aged less than 5 years - Sinha, Anju; Sazawal, Sunil; Kumar, Ramesh; Sood, Seema; Reddaiah, Vankadara P; Singh, Bir; Rao, Malla; Naficy, Abdolla; Clemens, John D; Bhan, Maharaj K (The Lancet (British edition), 1999)
Calculation of the incidence of typhoid fever during preschool years is important to define the optimum age of immunisation and the choice of vaccines for public-health programmes in developing countries. Hospital-based studies have suggested that children younger than 5 years do not need vaccination against typhoid fever, but this view needs to be re-examined in community-based longitudinal studies. We undertook a prospective follow-up study of residents of a low-income urban area of Delhi, India, with active surveillance for case detection. A baseline census was undertaken in 1995. Between Nov 1, 1995, and Oct 31, 1996, we visited 8172 residents of 1820 households in Kalkaji, Delhi, twice weekly to detect febrile cases. Blood samples were obtained from febrile patients, and those who tested positive for Salmonella typhi were treated with ciprofloxacin. 63 culture-positive typhoid fever cases were detected. Of these, 28 (44%) were in children aged under 5 years. The incidence rate of typhoid per 1000 person-years was 27·3 at age under 5 years, 11·7 at 5-19 years, and 1·1 between 19 and 40 years. The difference in the incidence of typhoid fever between those under 5 years and those aged 5–19 years, (15·6 per 1000 person-years [95% Cl 4·7–26·5]), and those aged 19–40 years (26·2 [16·0–36·3]) was significant (p<0·001 for both). The difference between the incidence of typhoid at 5–19 years and the incidence at 19–40 years was also significant (10·6 [6·3–14–8], p<0·001). Morbidity in those under 5 and in older people was similar in terms of duration of fever, signs and symptoms, and need for hospital admission. Our findings challenge the common view that typhoid fever is a disorder of school-age children and of adults. Typhoid is a common and significant cause of morbidity between 1 and 5 years of age. The optimum age of typhoid immunisation and the choice of vaccines needs to be reassessed.